2012
DOI: 10.5505/phd.2012.62681
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Internalized Stigma Level of Patients Attending to a Public and Private Psychiatric Institution

Abstract: ÖZETAmaç: Araştırma psikiyatrik hizmet sunan bir kamu kurumu ile özel bir psikiyatri hastanesine başvuran hastaların içselleştirilmiş damgalanma düzeylerinin karşılaştırılması ve içselleştirilmiş damgalanma düzeyini etkileyen değişkenlerin incelenmesi amacıyla yapılmıştır. Gereç ve Yöntem:2009 yılı Mart ayı içinde gerçekleştirilen tanımla-yıcı nitelikteki bu çalışmada etik kurul onayı alınmış olup, araştırma için damgalanmadan etkilenmiş olabileceği düşünülen bir kamu psikiyatri kurumu ve özel bir psikiyatri k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…Among psychiatric disorders, schizophrenia and bipolar disorder have been reported to be exposed to the highest levels of internalized stigma (33). In a study of 100 psychiatric patients mainly with psychotic disorders and affective disorders admitted to governmental or private institutions, again moderate levels of internalized stigma were reported, although to a lesser degree than in our study (34). Another observation in our study involves a negative and moderately significant correlation between the ISMI and MSPSS scores.…”
Section: Discussionsupporting
confidence: 49%
“…Among psychiatric disorders, schizophrenia and bipolar disorder have been reported to be exposed to the highest levels of internalized stigma (33). In a study of 100 psychiatric patients mainly with psychotic disorders and affective disorders admitted to governmental or private institutions, again moderate levels of internalized stigma were reported, although to a lesser degree than in our study (34). Another observation in our study involves a negative and moderately significant correlation between the ISMI and MSPSS scores.…”
Section: Discussionsupporting
confidence: 49%
“…This finding was similar to the results of our study. In the studies by Tel and Pınar (2012) (14), Coşkun and Güven Caymaz (2012) (15), ISMI total and subscale scores were lower than the results of this study, but it was determined that patients perceived internal stigmatization at an above medium level (14,15). In a study conducted with forensic mental illness, the self-stigmatization perceptions of patients with a diagnosis of psychotic disorder and with a high level of social withdrawal were found to be higher (11).…”
Section: Discussionmentioning
confidence: 39%
“…This result was slightly above the internalized stigma total average score (29-116), so it can be said that the patients experienced medium level internalized stigmatization. In some studies, mental illness' levels of internalized stigmatization have been found to be high according to their illness diagnosis, while in others it was determined that patients perceived stigmatization at a medium level of the levels of internalized stigmatization (14)(15)(16). It was determined that Özçelik's patients (76.12±17.15) perceived internalized stigmatization at above medium level.…”
Section: Discussionmentioning
confidence: 99%
“…When the literature on this subject is reviewed, it is seen that the results of the studies examining the relationship between the duration of illness and stigmatization are contradictory, but in most of the studies, it has been reported that there is no significant relationship between the duration of illness and perceived and experienced stigmatization. [22,23] In our study, the use of a sample of patients followed by a community mental health center may have led to results of individuals with a relatively better prognosis and under treatment. The negative correlation between the duration of illness and perceived discrimination may be related to the fact that the longer the duration of illness, the less likely it is to be affected by negative situations and the better integration and adaptation capacity to the society.…”
Section: Discussionmentioning
confidence: 98%